Necrotizing Enterocolitis in Newborns: Diagnosis, Etiology, Management, Prevention, Complications and their Relation to Future Sport Performance - Uszok, Zofia; Łepik, Michał; Rosiak, Krzysztof; Płeska, Kacper; Reguła, Kacper; Waloch, Kamil; Wojtania, Joanna; Piaszczyński, Szymon; Szymański , Bartłomiej; Czajka, Andrzej (Quality in Sport, 2024)
Necrotizing enterocolitis (NEC) is a serious gastrointestinal condition that primarily affects premature infants, although it can also occur in full-term infants. It is characterized by inflammation and injury of the intestinal tissue, which can progress to necrosis and perforation of the bowel. NEC is a leading cause of morbidity and mortality in neonatal intensive care units (NICUs), particularly among very low birth weight infants. Diagnosis of NEC is based on clinical signs and symptoms, radiographic findings, and laboratory tests. Management of NEC involves a multidisciplinary approach, including supportive care, medical therapy, and surgical intervention when necessary. Supportive care includes bowel rest, intravenous fluids, and nutritional support. Medical therapy may include antibiotics, gastric decompression, and parenteral nutrition. Surgical intervention may be required for infants with intestinal perforation, severe NEC, or complications such as intestinal stricture or short bowel syndrome. This condition and its complications may carry consequences for life and especially sport performance in the child’s future. Strategies for preventing NEC include promoting breastfeeding, avoiding unnecessary antibiotic exposure, minimizing enteral feeding interruptions, practicing strict infection control measures, and implementing protocols for gradual feeding advancement in premature infants. Overall, NEC is a complex and multifactorial disease that poses significant challenges in neonatal care. Early recognition, prompt intervention, and comprehensive management are essential for optimizing outcomes for affected infants. Further research is needed to better understand the pathophysiology of NEC and to develop more effective prevention and treatment strategies.